Parathyroid hormone alleviates non-alcoholic liver steatosis via activating the hepatic cAMP/PKA/CREB pathway - Feng, Xu; Xiao, Ye; Guo, Qi; Peng, Hui; Zhou, Hai-Yan; Wang, Jian-Ping; Xia, Zhu-Ying (Frontiers in Endocrinology, 2022)
Non-alcoholic fatty liver disease (NAFLD), hallmarked by liver steatosis, is becoming a global concern, but effective and safe drugs for NAFLD are still lacking at present. Parathyroid hormone (PTH), the only FDA-approved anabolic treatment for osteoporosis, is important in calcium-phosphate homeostasis. However, little is known about its potential therapeutic effects in other diseases. Here, we report that intermittent administration of PTH ameliorated non-alcoholic liver steatosis in diet-induced obese (DIO) mice and db/db mice, as well as fasting-induced hepatic steatosis. In vitro, PTH inhibits palmitic acid-induced intracellular lipid accumulation in a parathyroid hormone 1 receptor (PTH1R)-dependent manner. Mechanistically, PTH upregulates the expression of genes involved in lipid β-oxidation and suppresses the expression of genes related to lipid uptake and de novo lipogenesis by activating the cAMP/PKA/CREB pathway. Taken together, our current finding proposes a new therapeutic role of PTH on NAFLD.